The World Bank Annual Report 2009 : Year in Review (World Bank, 2009)
The World Bank Group's work focuses on achievement of the eight Millennium Development Goals (MDGs). The goals call for eliminating poverty and achieving inclusive and sustainable globalization. The MDGs lay out a blueprint for the World Bank Group, setting its priorities and measuring its results. The World Bank is the world's largest funder of education; the world's largest external funder of the fight against HIV/AIDS; a leader in the fight against corruption worldwide; a strong supporter of debt relief; and the largest international financier of biodiversity, water supply, and sanitation projects. The recipients of the World Bank Group's fiscal 2008 financial commitments are using the funds in more than 670 projects, many of them collaborative efforts of two or more of the affiliates. The projects are designed to overcome poverty and enhance growth by improving education and health services, promoting private sector development, building infrastructure, and strengthening governance and institutions. They are practical plans to help developing countries move from poverty and become more competitive in a globalizing world. The Bank Group is also preparing a strategic framework on climate change and development - a plan for integrating climate change and development challenges without compromising growth and poverty reduction efforts. The framework will include priorities, approaches, and a road map for action in helping countries mitigate or adapt to climate change. In addition, the Bank Group has set a goal of scaling up its portfolio of investments in renewable energy and energy efficiency projects by an annual average of 20 percent through 2010.